Nucleotide sequence and expression of cheF, an essential gene for chemotaxis in Bacillus subtilis. - Ying, C W (1989)
The cheF gene, which is involved in chemotaxis in Bacillus subtilis, has been cloned, expressed, and sequenced. This gene is contained in a 0.7-kilobase PstI DNA fragment that was isolated from a lambda Charon 4A B. subtilis chromosomal DNA library. This fragment was subcloned into the expression vector pSI-1 and shown to complement the cheF mutation both for chemotaxis and for methanol production in response to the addition of attractants. Plasmid-encoded DNA expression in B. subtilis maxicells indicated that a membrane-associated polypeptide of 20-kilodaltons was expressed from this 0.7-kilobase DNA. The nucleotide sequence of this DNA fragment was determined, and an open reading frame capable of encoding a putative 175-amino-acid protein (Mr 20,002) was identified. In an effort to understand the function of the cheF protein, the dosage of the cheF gene product was varied by altering the concentration of IPTG (isopropyl-beta-D-thiogalactopyranoside) during growth. In the presence of high concentrations of IPTG, chemotaxis was inhibited and methanol production was impaired.